Study on dynamic strength criterion of sandstone under the coupling influence of confining pressure, bedding angle and impact pressure - Wenbing Fan; Junwen Zhang; Yang Yang; Jiaqi Wang; Lin Mao; Shaokang Wu; Yang Zhang; Xukai Dong; Yifan Huang; Chuanzhong Jiang (Geomechanics and Geophysics for Geo-Energy and Geo-Resources)
Abstract The traditional Mohr–Coulomb and Hoek–Brown strength criteria exhibit limitations in characterizing the strength behavior of layered sandstone under dynamic loading. Specifically, these criteria fail to adequately account for the coupled effects of confining pressure, bedding angle, and impact pressure on the dynamic evolution of sandstone strength parameters, including the internal friction angle (φ), cohesion (c), and Hoek–Brown parameter (m). To address this issue, this study systematically integrates experimental investigations and theoretical modeling to establish a dynamic strength criterion that incorporates multifactorial coupling effects. Using a modified split Hopkinson pressure bar (SHPB) system, uniaxial dynamic impact tests and three-dimensional dynamic-static combined loading tests were conducted on sandstone specimens with varying bedding angles (0°, 30°, 45°, 60°, 90°), confining pressures (0, 5, 10, 20 MPa), and impact pressures (0.8, 1.2, 1.6 MPa). Key experimental findings include: (1): As the impact pressure increased from 0.8 to 1.6 MPa, the cohesion (c) rose from 65.43 MPa to 80.99 MPa, the internal friction angle (φ) increased from 28.63° to 36.39°, and the Hoek–Brown parameter (m) surged from 5.81 to 12.23. (2): When the bedding angle increased from 0° to 90°, the cohesion (c) nonlinearly decreased from 65.43 MPa to 64.24 MPa, the internal friction angle (φ) declined from 28.63° to 26.01°, and the Hoek–Brown parameter (m) decreased from 5.81 to 5.68. Building on these results, enhanced strength criteria were proposed to explicitly integrate the coupling effects of confining pressure, bedding angle, and impact pressure. Theoretical strength values calculated using the improved criteria were compared with experimental measurements. Validation demonstrated that the modified Mohr–Coulomb criterion achieved an accuracy of 15%, while the refined Hoek–Brown criterion attained an accuracy of 10%. These findings conclusively demonstrate that the proposed criteria effectively describe the dynamic strength characteristics of sandstone under the combined influence of confining pressure, bedding angle, and impact pressure, providing a robust framework for stability analysis in deep rock engineering applications.